2015
DOI: 10.1186/s12864-015-1535-z
|View full text |Cite
|
Sign up to set email alerts
|

Poplar trees reconfigure the transcriptome and metabolome in response to drought in a genotype- and time-of-day-dependent manner

Abstract: BackgroundDrought has a major impact on tree growth and survival. Understanding tree responses to this stress can have important application in both conservation of forest health, and in production forestry. Trees of the genus Populus provide an excellent opportunity to explore the mechanistic underpinnings of forest tree drought responses, given the growing molecular resources that are available for this taxon. Here, foliar tissue of six water-deficit stressed P. balsamifera genotypes was analysed for variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 50 publications
3
50
0
9
Order By: Relevance
“…The results also showed an increase in the levels of isoleucine in the DT cultivars while aspartic acid levels were lower in the DT. A study on the drought response of Poplar trees found that isoleucine had the highest fold increase in DT Poplar trees as compared to the DS under drought stress (Hamanishi et al, 2015). This is in agreement with the results obtained in this study.…”
Section: Amino Acid Metabolismsupporting
confidence: 92%
See 1 more Smart Citation
“…The results also showed an increase in the levels of isoleucine in the DT cultivars while aspartic acid levels were lower in the DT. A study on the drought response of Poplar trees found that isoleucine had the highest fold increase in DT Poplar trees as compared to the DS under drought stress (Hamanishi et al, 2015). This is in agreement with the results obtained in this study.…”
Section: Amino Acid Metabolismsupporting
confidence: 92%
“…disrupts plant metabolism resulting in metabolic pathway reconfiguration, ensuring plant survival (Hamanishi et al, 2015). Plants have established innumerable strategies in response to drought (Ogbaga et al, 2014).…”
Section: Plant Metabolomicsmentioning
confidence: 99%
“…High variability in the expression of TCA‐cycle genes were also observed within Populus balsamífera genotypes subjected to drought. The leaves from drought‐stressed plants showed induction or repression in CS and MD genes depending on the genotype analyzed (Hamanishi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics has already been applied to evaluate and assess GM food resources such as soybean [35], rice [36], maize [37,38], wheat [39], tomato [40], poplar [41] and barley [42]. As the production of GM food resources is expected to increase, the importance and application of metabolomics in this area will increase as well.…”
Section: Current Opinion In Biotechnologymentioning
confidence: 98%